Analysis of MUC6 polymorphisms on the clinicopathologic characteristics of Asian patients with oral squamous cell carcinoma - Hua, Chun‐Hung; Chuang, Chun‐Yi; Chien, Yi‐Chung; Su, Chun‐Wen; Chen, Shuo‐Chueh; Liu, Liang‐Chih; Yang, Shun‐Fa; Yu, Yung‐Luen (Journal of cellular and molecular medicine, 2023)
Head and neck squamous cell carcinomas (HNSCCs) are generally associated with tobacco consumption, alcohol abuse or both. Mucins (MUCs) are high‐molecular‐weight glycoproteins produced by many epithelial tissues. Many studies have indicated that MUCs play an important role in cancer metastasis. MUC6 expression has been observed in gastric and oncocytic phenotypes and plays an important role during cancer progression. We found that levels of MUC6 are lower in Asian HNCC patients and affect the disease‐free survival of HNCC patients. Next, we investigated the combined effect of MUC6 polymorphisms and exposure to environmental carcinogens on the susceptibility to and clinicopathological characteristics of HNCC. Three single‐nucleotide polymorphisms (SNPs) of MUC6 (rs7481521, rs6597947 and rs61869016) were analysed using real‐time PCR. After adjusting for other co‐variants, we found that carrying a CC genotype at MUC6 rs6597947 led to a lower risk of developing oral squamous cell carcinoma (OSCC) than wild‐type carriers among non‐betel‐quid chewers. Moreover, male oral cancer patients who carried the AA + CC genotype at MUC6 rs6597947 had a lower risk of lymph node metastasis than other genotypes, suggesting a significant functional compromise and decompensated disease. Therefore, our findings suggest that genetic variations in MUC6 may correlate to OSCC and indicate the progression in OSCC patients.